Factor Affecting the Decision of Homeownership in Johor Bahru - Ishak, Izzaamirah (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the factors that may have influence to the decision of homeownership in the area of Johor Bahru. A total of 200 working individual had participated in this research by answering a set of questionnaire with 29 questions related to the homeownership determinant. The objectives of this research is to identify which factor among financial factors, locational attributes and structural attributes give the most impact towards homeownership decision. It is said that each individual has their own preferences for homeownership, so the researcher aims to identify that through this research. The decision of homeownership is measured by the buyers’ motivation to buy a house in the Johor Bahru area specifically. The findings of this research can create awareness and also provide meaningful knowledge to housing developers for their business while contributed to the public who interested on this research. Financial Factors, Homeownership, and Locational Attributes Structural Attributes